PERSEPSI DAN PREFERENSI MASYARAKAT TERHADAP FASAD BANGUNAN DI KORIDOR JALAN KI SAMAUN KOTA TANGERANG - Nur Sukma Suri; Agung Sugiri (Diponegoro University, 2015)
This research aims to discover people’s perceptions and preferences towards building façade. This research has used a mixed-method approach with the triangulation of data validation. In the analysis, a sequence-analysis method has been utilized, beginning from qualitative descriptive to quantitative one. Data were collected from in-depth-interview with several key persons like district official, officers of certain governmental departments, and questionnaire distribution to the people who have their daily activities in Ki SamaunStreet, which is part of Kota Lama area in Tangerang City. The findings of this study show that colors; architectural design; width and height of the buildings and building-‘s’ ornaments are the most important elements in building façade that can be used to comprehend the people’s perceptions and preferences. This study has found that there are similarities between people’s perceptions and preferences with the Kota Lama’s development plans. Both sides are of the opinion that the colors of the buildings are similar, unpleasant, and there are some buildings more stand out than the others. Both sides also perceive that the architectural style of the buildings no longer represents the Chinese culture. This makes the restoration work to reverse the façade back into its original form is essential. Both sides also recognize that building-‘s’ height and width are not in harmony, although the people think that renovation is not needed. Both sides also observe that there are no buildingswith similar ornaments; whilesignage is the main source of visual pollution and rearrangement of signage is needed.